Jet-flipping phenomenon under sluice gate - Ling, Qinxuan. (2011)
In this project, the purpose is to understand the scour, especially the reason for the jet flipping phenomenon which occur jet flow issuing from a submerged sluice gate. Jets issued from the sluice gate can produce two very different flow patterns depending on different experiment conditions. One is the bed jet which always attached itself to the sediment bed and at last the scour process can arrive at an equilibrium state. The other is the jet can suddenly change from bed to surface, then the jet flipping occurs leading to the sands in the sediment bed reactive after the equilibrium stage of scouring, and after some time it becomes to bed jet again. This is a cyclical process and an equilibrium state will never be reached.